A Pipette for High-Resolution Sampling and Delivery of pL Bio-Samples - Ziyang Han; Pengfei Gong; Hengxiang Su; Zehang Gao; Shilun Feng; Jianlong Zhao (Micromachines)
Conventional laboratory methods for handling valuable biological samples typically use pipettes or needles, which are prone to issues such as dead volume and sample waste. Furthermore, the sampling and processing of pathogenic bacteria, such as Escherichia coli (E. coli) in environmental wastewater, require labor-intensive procedures with multiple complex steps. To overcome these limitations, we developed a pipette integrated with a microfluidic chip for bacteria sampling and delivery. This pipette can provide the negative pressure to microfluidic chips for sampling, the constant temperature unit for biological reaction, and programs for automatic control (suction, heating, liquid discharge, and cleaning) and display. The droplet chip employs a cross-channel structure to generate droplets and incorporates a designated droplet storage and detection area. Utilizing this innovative device, we have demonstrated the generation, transportation, and storage of pL droplets, as well as quantitatively detected E. coli samples across various concentrations. The test results have demonstrated the overall reliability and data consistency of the system. Overall, our device achieves the precise sampling of pL volumes, offering a simple yet promising solution for the sampling and delivery of bio-samples in remote settings.